Compact two-port antenna with high isolation based on the defected ground for THz communication - Anubhav Kumar; Divya Saxena; Pankaj Jha; Navneet Sharma (Results in Optics, 2023)
The two-port antenna is designed for THz communication where isolation is achieved with the defective ground. The radiator of the two-port antenna is inspired by the half-cutting technology which reduces the size and makes it a compact antenna. The T-shaped stub and open-ended slot are used to modify the capacitive and inductive reactance which diminish and discontinued the surface current to improve the port isolation. The T-shaped stub improves the electric length of the ground and enhances the port isolation by up to 3.4 dB and open-ended slot in the ground is used to weaken the mutual current and create the non-uniform current which intensifications the port isolation up to 7.7 dB at 2.2 THz. The dimensions of the design is 100 µm × 105 µm and the edge distance of the antennas is only 0.20λ with maximum isolation is 30 dB at 2.2 THz. The bandwidth of the two-port antenna is 1.74 THz to 2.52 THz that can be applicable in wireless communication applications.